BANHO ULTRASSÔNICO DE POTÊNCIA VARIADA PARA SÍNTESE DE BIODIESEL - Haubert, Arlei Alberto (2017)
The incessant demand for renewable energies and sustainable models for the biofuels sector demands technological innovations, with the biodiesel manufacturing process growing as an alternative to the use of diesel, which is polluting and with the imminence of future scarcity. This research has as main objective the production of biodiesel of soybean oil assisted by ultrasonic waves of different powers. The Ultrasonic Bath presented consists of rectified feed, variable power circuit of 50 / 30W and piezoelectric transducer of 55W power and 100 ml becker coupled to the system for the synthesis of biodiesel. The equipment was aligned at the square wave frequency of 42.5 kHz and the ester content by mass of 96.5% was used as the reference for obtaining the biodiesel in accordance with ANP recommendations 30/2016 and 45/2014. At the power of 30W biodiesel was obtained in synthesis times of 40 and 45 minutes with ester contents of 97% ± 0.42 and 100.40% ± 0.00. At 50W power with times less than 20, 25 and 30 minutes with ester contents of 100.50 ± 0.14, 99.67 ± 0.45 and 100.33 ± 0.06, respectively. In this way, the ultrasonic waves act as catalysts thus reducing the time of synthesis. Biodiesel produced at 50 W of power for 20 minutes has a specific mass of 886.3 kg / m3, water content of 165.1 mg / kg, acid number of 0.4 KOH / g and induction time of the accelerated oxidation of 4.4 h. The total cost of the equipment is budgeted at US$ 165.28, which is 50% lower than the same type of equipment commercially available for this purpose. In this way, the use of the ultrasonic bath in the synthesis of biodiesel demonstrates to be economically viable and of adequate efficiency to the use.